Does stage of change predict outcome in a primary-care intervention to encourage an increase in fruit and vegetable consumption? - John, J; Yudkin, P; Neil, H; Ziebland, S (2003)
Our aim was to investigate the response of participants in different Stage of Change (SOC) groups to an intervention to increase fruit and vegetable consumption. Participants recruited from a primary-care health centre were entered into a trial investigating an intervention to increase fruit and vegetable consumption. A total of 729 men and women were randomized into intervention and control groups. Participants attended two appointments 6 months apart and completed postal questionnaires before each appointment. The questionnaire included SOC questions which were used to classify participants into 'pre-contemplation', 'contemplation' and 'action' groups at baseline and at follow-up. All intervention participants received a standard intervention to increase consumption of fruit and vegetables to at least five portions per day. After 6 months at the end of the trial control participants received the same intervention. The main outcome measures were the changes in plasma concentrations of antioxidant vitamins. Changes in self-reported fruit and vegetable intake were a secondary outcome measure. At baseline, 38% (113/297) of the intervention participants were described as being in the 'pre-contemplation' stage, 35% in 'contemplation' and 27% in 'action' groups. For control participants, 36% (112/310) were in 'pre-contemplation', 34% in 'contemplation' and 30% in 'action' groups. In the intervention groups, 50% (57/113) of 'pre-contemplators' moved to the 'action' stage and 37% (42/113) moved to 'contemplation'. There was little movement in the control 'SOC' groups between baseline and follow-up, other than a small drift to 'contemplation'. Overall, the intervention group reported a greater increase in fruit and vegetable consumption than the controls (mean difference in change of 1.4 daily portions; 95% confidence interval 1.2, 1.6; after adjustment for baseline intake and gender) and significantly greater changes were reported in all three intervention 'SOC' groups compared to the corresponding 'control' groups (P < 0.001 in each case). These results suggest that peoples' SOC may have little bearing on their success in increasing fruit and vegetable consumption.